Website Quality, Brand Image, dan E-WOM serta Pengaruhnya terhadap Online Purchase Intention Studi Pengunjung Website Berrybenka - Indana, Lutfi; Andjarwati, Anik Lestari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The high purchasing power of the people for fashion products is an opportunity for the company to create new business strategies to compete. One of the fashion brands in Indonesia is Berrybenka, which offers a variety of the latest and high-quality fashion needs. However, in consumer purchases made online through websites, there are still negative reviews about Berrybenka. This study aims to analyze the effect of website quality, brand image, and e-WOM on online purchase intentions. This study is focused on Berrybenka websites visitors as a sample with a nonprobability sampling technique. The questionnaire was taken to 200 respondents using a Likert scale. The data analysis technique used multiple linear regression. The results showed that website quality, the brand image had an influence on online purchase intentions and e-WOM had no effect on online purchase intentions.